2005
DOI: 10.1111/j.1469-8137.2005.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of penetrance and expressivity of RNAi‐mediated silencing of the Arabidopsis phytoene desaturase gene

Abstract: Summary• RNA interference (RNAi) is of great value in plant functional genomics. However, the absence of RNAi phenotypes and the lack of uniform level of RNAi silencing has complicated gene identification. Here, the penetrance and expressivity of RNAimediated silencing of the phytoene desaturase ( PDS ) gene in Arabidopsis thaliana were examined quantitatively to provide a reference for the likely severity and distribution of silencing effects.• Arabidopsis plants were transformed with an RNAi construct target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…A phenotypic series was obtained from the RNAi lines with a full spectrum of the effect of RNAi (weak, intermediate, and strong) on gene expression, which is in agreement with the results in Arabidopsis (Chuang and Meyerowitz, 2000;Wang et al, 2005) and tomato (Xiong et al, 2005). Part of the variation of the RNAi effect can be explained by transgene copy number and/or positional effects of particular DNA insertion events.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A phenotypic series was obtained from the RNAi lines with a full spectrum of the effect of RNAi (weak, intermediate, and strong) on gene expression, which is in agreement with the results in Arabidopsis (Chuang and Meyerowitz, 2000;Wang et al, 2005) and tomato (Xiong et al, 2005). Part of the variation of the RNAi effect can be explained by transgene copy number and/or positional effects of particular DNA insertion events.…”
Section: Discussionsupporting
confidence: 81%
“…However, our results suggest that the severity of phenotypes is not related to the transgene copy number, because both single and multiple copy lines with extensive DNA rearrangements showed a mutant phenotype. Chuang and Meyerowitz (2000) and Wang et al (2005) also found no relationship between severity of the phenotype and transgene copy number in Arabidopsis. In contrast, Kerschen et al (2004) described that multicopy RNAi Arabidopsis lines reduced target mRNA levels to a lesser extent and with more variability between lines than did singlecopy lines.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is a smaller number of genes than found in our studies, one reason being that ~66% fewer genes were surveyed in their experiments. Surprisingly, there were very few similarities among the 596 differentially regulated genes in pds3 compared to imW or to NF-treated tissues: correlation between PDS activity and phenotype is supported by the observation that PDS antisense and RNAi mutants, both of which have partial downregulation of PDS, have variegated phenotypes, 22,23 and by our demonstration that variegated Arabidopsis can be produced by treatment of WT with low concentrations of NF, again partially inhibiting PDS activity. 17 If our assumption is correct that plastid phenotype can be determined via an impact of PDS activity on excitation pressure, then it can be hypothesized that retrograde signaling varies in a qualitative or quantitative manner depending on the overall excitation pressure that is present in the developing plastids in a cell.…”
Section: A Hypothesis: the Redox State Of The Pq Pool Acts As A Rheosmentioning
confidence: 80%
“…To demonstrate the applicability of the antisense ODN technology in plants, we chose the nucleusencoded pds and cab genes as model genes. The pds gene has been used as a marker in several studies on gene silencing in plants (Chamovitz et al, 1993;Kumagai et al, 1995;Lindgren et al, 2003;Tao and Zhou, 2004;Wang et al, 2005Wang et al, , 2009. pds encodes a key enzyme in carotenoid biosynthesis, which converts phytoene to the colored j-carotene in a two-step desaturation reaction (Bartley and Scolnik, 1995).…”
Section: Uptake and Transport Of Odns In Plants As Investigated By Flmentioning
confidence: 99%